Role of c-Jun N-Terminal Protein Kinase 1/2 (JNK1/2) in Macrophage-Mediated MMP-9 Production in Response to Moraxella catarrhalis Lipooligosaccharide (LOS) - Hassan, Ferdaus (Public Library of Science, 2012)
Moraxella catarrhalis is a Gram negative bacterium and a leading causative agent of otitis media (OM) in children. Recent reports have provided strong evidence for the presence of high levels of matrix metalloproteinase (MMPs) in effusion fluids from children suffering with OM, however, the precise mechanisms by which MMPs are generated are currently unknown. We hypothesized that MMPs are secreted from macrophages in the presence of M. catarrhalis lipooligosaccharide (LOS). In this report, we demonstrate that in vitro stimulation of murine macrophage RAW 264.7 cells with LOS leads to secretion of MMP-9 as determined by ELISA and zymogram assays. We have also shown that inhibition of ERK1/2 and p38 kinase completely blocked LOS induced MMP-9 production. In contrast, inhibition of JNK1/2 by the specific inhibitor SP600125 actually increased the level of expression and production of MMP-9 at both mRNA and protein levels, respectively by almost five fold. This latter result was confirmed by knocking down JNK1/2 using siRNA. Similar results have been observed in murine bone marrow derived macrophages in vitro. In contrast to and in parallel with the LOS-induced increased levels of MMP-9 in the presence of SP600125, we found a corresponding dose-dependent inhibition of TIMP-1 (tissue inhibitor of matrix metalloproteinase-1) secretion. Results of subsequent in vitro studies provided evidence that when JNK1/2 was inhibited prior to stimulation with LOS, it significantly increased both the extent of macrophage cell migration and invasion compared to control cells or cells treated with LOS alone. The results of these studies contribute to an increased understanding of the underlying pathophysiology of OM with effusion in children.